Cannabidiol Demonstrates Remarkable Efficacy in Treating Multidrug-Resistant Enterococcus Faecalis Infections In Vitro and In Vivo - Hongsing, Parichart; Ngamwongsatit, Natharin; Kongart, Chomlak; Nuiden, Nida; Phairoh, Krittapat; Wannigama, Dhammika Leshan (Trends in Sciences, 2024)
The growing prevalence of multidrug-resistant Enterococcus faecalis infection has become a global concern. There is a demand for alternative antibacterial agents, such as herbal alternatives, such as Cannabidiol, that are cost-effective, non-toxic and efficient. This study investigates the Minimum Inhibitory Concentration (MIC) for planktonic cells and the Minimum Biofilm Eradication Concentration (MBEC) for biofilm formation in multidrug- resistance isolates of E. faecalis isolates, particularly focusing cannabidiol activity. E. faecalis isolates with strong biofilm presence, vancomycin, levofloxacin, and daptomycin displayed high MIC and MBEC values. Cannabidiol exhibited a significantly lower MIC (1 μg/mL) for planktonic cells and a low MBEC (2 μg/mL). Moreover, at low concentrations (2 µg/mL), cannabidiol demonstrated notable reductions in biofilm biovolume, bacterial cell viability and colony-forming unit compared to vancomycin, levofloxacin, and daptomycin. The mice treated with cannabidiol (100 mg/kg) exhibited a significant reduction in E. faecalis bacterial load in internal organs and increased the survival. In conclusion, the findings underscore the promising antibiofilm properties of cannabidiol against E. faecalis, indicating its potential as a novel therapeutic agent. HIGHLIGHTS The increase of multidrug-resistant Enterococcus faecalis infection has become a global concern. Cannabidiol (CBD) is an herbal alternative with potential antibacterial activity. Our study result shows the promising antibiofilm properties of cannabidiol against E. faecalis in vitro and in vivo. GRAPHICAL ABSTRACT